Adaptive Capacity Of Women In Poor Households During The Covid Pandemic Period In Indonesia (Kapasitas Adaptasi Perempuan Dalam Rumah Tangga Miskin Selama Masa Pandemi COVID In Indonesia) - Keukeu Komarawati; Muhammad Fadhil Nurdin; Rachmat Koesnadi; M. Ikbal Sonuari (Aliansi, 2022)
The COVID-19 pandemic has made women vulnerable to problems because they have low incomes, low savings, and tend not to have adequate protection due to their majority status as informal workers. In 2020, Indonesia has a women population of 133.54 million. The Central Statistics Agency for Indonesia shows that the percentage of poor women (Head Count Index) in March 2020 was 9.96 percent. This means that 9.96 percent of the total women population in Indonesia is poor. Women's poverty will also be evident in households with a women head of household. The percentage of women household heads is mostly found in poor families. In March 2020, 15.88 percent of women were heads of households with poor status in Indonesia. Disaster management which was later realized in the form of policies in the form of health protocols, Large-Scale Social Restrictions, and the determination of WFH (work from home) and SFH (school from home) activities created a lot of pressure for women, plus the burden on the family economy that poor women had to accept in Indonesia. The adaptive capacity possessed by women allows them to adapt to changes, giving rise to adaptive capacity. Adaptive capacity refers to the proactive (ex-ante) or preventive actions that people use to learn from past experiences, anticipate future risks and adapt to current conditions. In this article, we will discuss the importance of economic development and social capital as part of a set of adaptive capacities for women in poor families during the Covid-19 pandemic which is supported by communities, stakeholders, and existing policies in Indonesia. Pandemi COVID-19 membuat perempuan rentan mengalami permasalahan karena mereka memiliki pendapatan yang rendah, tabungan yang rendah, dan cenderung tidak memiliki proteksi yang memadai akibat statusnya yang mayoritas sebagai tenaga kerja informal. Pada tahun 2020, Indonesia memiliki jumlah penduduk perempuan sebanyak 133,54 juta. Badan Pusat Stastitik Indonesia menunjukkan bahwa persentase penduduk miskin (Head Count Index) perempuan pada Maret 2020 sebesar 9,96 persen. Artinya, 9,96 persen dari seluruh penduduk perempuan di Indonesia berstatus miskin. Kemiskinan perempuan juga akan tampak nyata pada rumah tangga dengan kepala rumah tangga perempuan. Persentase kepala rumah tangga perempuan banyak ditemui pada keluarga miskin. Pada Maret 2020, 15,88 persen perempuan merupakan kepala rumah tangga dengan status miskin di Indonesia. Penanggulangan bencana yang kemudian diwujudkan dalam bentuk kebijakan berupa protokol kesehatan, Pembatasan Sosial Berskala Besar, dan penetapan kegiatan WFH (work from home) serta SFH (school from home) membuat banyak tekanan bagi para perempuan, ditambah beban perekonomian keluarga yang harus diterima oleh perempuan miskin di Indonesia. Kemampuan adaptasi yang dimiliki oleh perempuan memungkinkan mereka beradaptasi dengan perubahan sehingga menimbulkan kapasitas adaptif. Kapasitas adaptif mengacu pada tindakan proaktif (ex-ante) atau pencegahan yang digunakan orang untuk belajar dari pengalaman masa lalu, mengantisipasi risiko di masa depan dan menyesuaikan diri dengan kondisi yang saat ini dialami. Dalam Artikel ini akan membahas pentingnya pembangunan ekonomi dan modal sosial sebagai salah satu bagian dari seperangkat kapasitas adaptif bagi perempuan dalam keluarga miskin selama Masa Pandemi Covid-19 yang didukung oleh komunitas, stakeholder dan kebijakan yang ada di Indonesia.